Rancangan Sistem Informasi Perpustakaan Berbasis Web Pada SMK Negeri 1 Tanjungpinang - Chandra, Rio; Dewayani, Ery (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
Technology that is now growing rapidly is widely used by the community for various activities, such as administrative activities. Of the many administrative activities that exist, the library is one of them that requires information technology in data management. The library is a building of an institution or agency that has the task of providing, compiling, and managing various collections of books. SMK Negeri 1 Tanjungpinang is one of the schools that still processes library data manually, which still does not utilize existing information technology. Data collection that is still done manually will cause problems, where data collection is slow and inefficient. Therefore, the design of this library information system will assist the administrative activities of SMK Negeri 1 Tanjungpinang by having a library data management website. This is useful for librarians in facilitating all data management processes, including making membership cards, the process of making reports, making and collecting data on borrowing and returning books. Making a web-based library information system at SMK Negeri 1 Tanjungpinang using the laravel framework with mysql database.